Reducing the Company’s Insolvency: How suspension of debt payment obligation and bankruptcy proceedings help the company? (Faculty of Law Universitas Negeri Semarang, 2022)
Corporate insolvency will have an unfavorable effect on the country's economy. Currently many companies are facing the threat of bankruptcy applications in the Commercial Court because difficulty of paying the company's debts to its creditors. In the midst of the situation the number of Covid-19 cases that occurred in Indonesia, it has a negative impact with the decline in the performance of business actors due to the crisis. From that situation, it results in a decrease in the amount of income to the difficulty of paying debts or credit to creditors. To reduce the increase in insolvency, the government seeks the enactment of a moratorium on PKPU and Bankruptcy whose implementation will pay attention to the development of Covid-19 pandemic conditions. This research aims to find out how the implications in implementing a moratorium on PKPU and Bankruptcy in order to reduce the company's insolvency and how its legal protection efforts for creditors and debtors. This research is Normative juridical with a Statute Approach. The results of this study are the implications that will occur in the enactment of the moratorium on PKPU and Bankruptcy and legal protection for the parties under Law No. 37 of 2004 on Bankruptcy and Delay of Debt Payment Obligations. By fulfilling the terms and conditions as intended, the conclusion obtained is that the implementation of the moratorium has a positive and negative impact on the parties and obtains protection and is justified by applicable law but must be in accordance with the applicable provisions.